Exploring public attitudes of continuing care retirement communities in China: a sentiment analysis of China’s social media Weibo - Wang, Xuechun; Xia, Bo; Chen, Qing; Skitmore, Martin; Liu, Huiming (Frontiers in Public Health, 2025)
Introduction The traditional family responsibility system faces challenges as China undergoes rapid demographic shifts with an increasingly older population. Recognizing the potential of market-driven senior care, Continuing Care Retirement Communities (CCRCs) have emerged as a significant alternative. However, cultural stigmas and concerns about the quality, services, and health of older adults in these facilities raise questions over their broad acceptance. Methods This study examines public sentiment toward CCRCs through sentiment analysis of 1,027,295 pre-processed Weibo posts. Utilizing Natural Language Processing (NLP) combined with fine-grained sentiment analysis and the Term Frequency-Inverse Document Frequency algorithm, the attitudes and emotions reflected in each data point are analyzed, identifying key contributing factors, and exploring the underlying reasons. Results and discussion The results reveal a predominantly positive sentiment toward CCRCs, emphasizing factors such as the living environment and government involvement. However, areas of concern, such as potential fraud and health and safety issues, remain. These findings both shed light on the public’s acceptance or resistance to CCRCs for stakeholders and highlight the potential of social media analysis in shaping older people’s care perceptions in today’s China.